Prognostic value of CD166 expression in cancers of the digestive system: a systematic review and meta-analysis. - Chao Ni; Zhigang Zhang; Xiaotao Zhu; Yang Liu; Dihong Qu; Ping Wu; Jian Huang; A-xiang Xu (PLoS ONE)
Objective Many studies have reported the prognostic predictive value of CD166 as a cancer stem cell marker in cancers of the digestive system; however, its predictive value remains controversial. Here, we investigate the correlation between CD166 positivity in digestive system cancers and clinicopathological features using meta-analysis. Methods A comprehensive search in PubMed and ISI Web of Science through March of 2013 was performed. Only articles containing CD166 antigen immunohistochemical staining in cancers of the digestive system were included,including pancreatic cancer, esophageal cancer, gastric cancer and colorectal cancer. Data comparing 3- and 5-year overall survival along with other clinicopathological features were collected. Results Nine studies with 2553 patients who met the inclusion criteria were included for the analysis. The median rate of CD166 immunohistochemical staining expression was 56% (25.4%-76.3%). In colorectal cancer specifically, the results of a fixed-effects model indicated that CD166-positive expression was an independent marker associated with a smaller tumor burden (T category; RR = 0.93, 95%, CI: 0.88-0.98) but worse spread to nearby lymph nodes (N category; RR = 1.17, 95% CI: 1.05-1.30). The 5-year overall survival rate was showed relationship with cytoplasmic positive staining of CD166 (RR = 1.47 95% 1.21-1.79), but no significant association was found in the pool or any other stratified analysis with 3- or 5- year overall survival rate. Conclusion Based on the published studies, different cellular location of CD166 has distinct prognostic value and cytoplasmic positive expression is associated with worse prognosis outcome. Besides, our results also find CD166 expression indicate advanced T category and N-positive status in colorectal cancer specifically.